Combined Use of Fecal Biomarkers in Inflammatory Bowel Diseases: Oncostatin M and Calprotectin - Cao Y (Dove Medical Press, 2021)
Ying Cao,1,* Yibei Dai,1,* Lingyu Zhang,1 Danhua Wang,1 Wen Hu,2 Qiao Yu,3 Xuchu Wang,1 Pan Yu,1 Weiwei Liu,1 Ying Ping,1 Tao Sun,1 Yiwen Sang,1 Zhenping Liu,4 Yan Chen,3 Zhihua Tao1 1Department of Laboratory Medicine, Zhejiang University School of Medicine Second Affiliated Hospital, Hangzhou, People’s Republic of China; 2National Clinical Research Center for Infectious Diseases, Zhejiang University School of Medicine First Affiliated Hospital, Hangzhou, People’s Republic of China; 3Center for Inflammatory Bowel Diseases, Department of Gastroenterology, Zhejiang University School of Medicine Second Affiliated Hospital, Hangzhou, People’s Republic of China; 4Department of Laboratory Medicine, the First People’s Hospital of Yuhang District, Hangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yan Chen; Zhihua Tao Tel +86 571 8778 3752Fax +86 571 8689 8730Email chenyan72_72@zju.edu.cn; zrtzh@zju.edu.cnBackground: Fecal biomarkers have emerged as one of the most useful tools for clinical management of inflammatory bowel disease (IBD). Oncostatin M (OSM), like fecal calprotectin (FC), is highly expressed in the inflamed intestinal mucosa which may have potential usefulness. We aimed to evaluate the additional utility of these two fecal biomarkers for IBD diagnosis, activity, and prediction of infliximab response over FC alone.Methods: In group 1, 236 IBD patients (145 Crohn’s disease, 91 ulcerative colitis), 50 disease controls, and 32 healthy controls were recruited for IBD diagnosis and activity. In group 2, baseline stool samples were collected from 62 patients to predict infliximab response at week 28 and 52. The performance of fecal biomarkers for IBD management was assessed by the area under the receiver operating characteristic curve (AUC).Results: Fecal OSM and FC levels were increased in IBD patients and were positively correlated with clinical and endoscopic activity. Their combination showed a better ability for disease diagnosis (AUC = 0.93) and slightly improved the capability to identify mucosal healing (AUC = 0.923). Baseline OSM and FC levels were elevated in non-responders at week 28 and 52. The AUCs of OSM, FC, and their combination to predict therapeutic response were 0.763, 0.834, and 0.859 at week 28, 0.638, 0.661, and 0.704 at week 52, respectively. Combined use of fecal and blood biomarkers improved predictive accuracy with an AUC of 0.919 at week 28 and 0.887 at week 52.Conclusion: In addition to FC, OSM is a novel fecal biomarker, and their combination is more beneficial for disease diagnosis and prediction of infliximab response but not for disease activity in IBD patients. Further larger-scale studies are required to confirm our findings.Keywords: inflammatory bowel disease, fecal biomarkers, oncostatin M, calprotectin, diagnosis, activity, infliximab response